A systematic literature review of how mutation testing supports quality assurance processes. (16th July 2018) - Zhu, Qianqian; Panichella, Annibale; Zaidman, Andy
Summary: Mutation testing has been very actively investigated by researchers since the 1970s, and remarkable advances have been achieved in its concepts, theory, technology, and empirical evidence. While the most influential realisations have been summarised by existing literature reviews, we lack insight into how mutation testing is actually applied. Our goal is to identify and classify the main applications of mutation testing and analyse the level of replicability of empirical studies related to mutation testing. To this aim, this paper provides a systematic literature review on the application perspective of mutation testing based on a collection of 191 papers published between 1981 and 2015. In particular, we analysed in which quality assurance processes mutation testing is used, which mutation tools and which mutation operators are employed. Additionally, we also investigated how the inherent core problems of mutation testing, ie, the equivalent mutant problem and the high computational cost, are addressed during the actual usage. The results show that most studies use mutation testing as an assessment tool targeting unit tests, and many of the supporting techniques for making mutation testing applicable in practice are still underdeveloped. Based on our observations, we made 9 recommendations for future work, including an important suggestion on how to report mutation testing in testing experiments in an appropriate manner. Abstract : This paper provides a systematic literature review on the application perspective of mutation testing based on a collection of 191 papers published between 1981 and 2015. In particular, we analysed which quality assurance processes mutation testing is used and which mutation tools and mutation operators are employed.